KARAKTERISASI KOMPOSIT EDIBLE FILM BUAH KOLANG-KALING (Arenge Pinnata) DAN LILIN LEBAH (Beeswax) [Characteristic of Composite Edible Film from Palm Ftuit (Arenge pinnata) and Beeswax] - Budi Santoso (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
The objective of this research was to study of the characteristics of edible film after addition of different concentrations of kolang-kaling and beeswax. The research used of Factorial Block Randomized Design with two treatments and each treatment was replicated three times. The first treatment was concentrations of the kolang-kaling (5%, 10%, 15% and 20%), and the second treatment was concentrations of the beeswax (0%, 0,5%, 1%, and 1,5%). The parameters were water content, tensile strength, elongation percentage, thickness, and water vapor transmission rate. The result showed that the addition of different concentrations of kolang-kaling and beeswax significantly afected the water content, tensile strength, elongation percentage, thickness, and water vapor transmission rate. The thickness increased with the increasing concentrations of kolang-kaling and beeswax. The water vapor transmission rate, tensile strength, and elongation percentage were decreased. The tensile strength, elongation percentage, thickness, and water vapor transmission rate of edible film were 0,342 Kgf cm-2, 52,5%, 0,025 mm and 53,439 gm-2hari-1 respectively. The best treatment was achived by using concentration of kolang-kaling at 5% and concentration of beeswax at 1,5%. Key words : Edible film, kolang-kaling, beeswax